Digital Leadership in Higher Education - Ulf-Daniel Ehlers (Ali Khorsandi Taskoh, 2021)
The issue "digital leadership" in higher education (HE) is challenging in two ways: Firstly, it is unclear whether we talk about the concepts of "digital leadership" or rather those of "leadership in the digital age". Secondly, it is an urgent topic: An increasing number of higher education institutions (HEIs) are involved in permanent change processes. This leads to their managers struggling to build and implement a coherent strategy for the institutions' digital transformation processes that is also externally visible. Despite managers occupying a key role for successful change processes, surprisingly we have little research on digital transformation processes in HEIs. Whereas other research fields (e.g. management, military) can rely on a rich base of empirical research on the topic of leadership, there is a lack of research for "leadership in education". Furthermore, only a few attempts exist to date (and to the author's knowledge) that aim at identifying the dimensions of (good) HE-leadership in the light of the increasing digital pressure for change. The aim of this paper is to conduct a status quo analysis thereby undertaking a first attempt to provide a systematization of potential fields of action. HEIs should pay close attention to these fields to avoid switching back and forth between the various "trending" digital strategies. We present a possible framework for leading the digitalization in an HE context.